MAGNETIC FIELD MEASUREMENT USING PHYPHOX MAGNETOMETER AND SOLENOID WITH BEACH SAND CORE DEMONSTRATION METHOD AS PROJECT-BASED LEARNING IN HIGH SCHOOL - Sukoco, Rubi
This research has applied information technology in physics learning at high school through project-based learning (PBL) with a focus on magnetic field measurement. This method has used Phyphox magnetometer integrated with solenoid demonstration method using beach sand core as a learning tool. The objectives of the research were to measure the value of the magnetic field at a point outside but near the solenoid with a variation of the solenoid core material, namely beach sand, understand that the relationship of changes in the solenoid core can affect the strength of the magnetic field produced, test the results with the parameters that affect it and introduce how to measure the magnetic field practically. This research focused on the development of educational technology by utilizing a smartphone as a magnetic field measuring device through the Phyphox application. Data was collected through measurements using a Phyphox magnetometer and a solenoid demonstration experiment with a beach sand core. The measurement results and data analysis were used to evaluate the effectiveness of the proposed learning approach. The Phyphox magnetometer provides magnetic field data with a sampling rate of 50 data points per second. Measurements of the magnetic field on the Earth's surface yielded a result of 46.06 ?T. This value is relevant and corresponds to the reference range of the average Earth's magnetic field intensity, which is between 25 ?T and 65 ?T. A solenoid demonstration with 300 turns, a current strength of 0.089 A, and a voltage of 3 volts generates a magnetic field. This field has been adjusted by subtracting the background value for air (empty) as the core material, resulting in (0.093±0.008) ?T. The magnetic field measurements for the East Pangandaran beach sand core are (3.068±0.003) ?T, Cikambulan beach sand core is (3.244±0.024) ?T, Batukaras beach sand core is (8.903±0.324) ?T, Batu Hiu beach sand core is (7.491±0.064) ?T, and Madasari beach sand core is (0.844±0.005) ?T. Additionally, for the solenoid with an iron core, the magnetic field is (47.163 ± 0.063) ?T. Therefore, the contribution of beach sand cores to the magnetic field intensity, from lowest to highest, is as follows: Madasari beach, East Pangandaran beach, Cikambulan beach, Batu Hiu beach, and Batukaras beach. These results align with the sequence of the density of each beach sand and the content of magnetic materials that easily adhere to permanent magnets. This research has practical implications in the development of physics learning methods that are more varied and interactive at the high school level. The results can be a guide for physics teachers to improve the quality of learning by utilizing simple technology and project-based learning.